Housing and Unhousing Tradition: Linda Hogan’s Power and Marilynne Robinson’s Housekeeping - Limpár, Ildikó (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Linda Flogan’s Power and Marilynne Robinson’s Housekeeping have generated very different discourses, although the numerous similarities between the two contemporary novels, I am convinced, call for an analysis that would place at last the ethnic and feminist interpretations in one house. One of the most striking shared components is a new and surprisingly similar concept of the house, an important yet not very elaborated metaphor in Power, and a central metaphor in Housekeeping. Furthermore, in both novels the story is narrated in first person singular by a young girl (Omishto in Power and Ruth in Housekeeping), who aims at following the path marked out for her by a mother-substitute aunt (Ama in Power and Sylvie in Housekeeping). Both novels present initiation stories of girls; both initiations are, in addition, connected to the choice about a way of life, based on an understanding of nature’s role in the world as opposed to that of civilization. As human relation to nature is a central theme in American literature, it is no wonder that both novels appear with the claim of forming part of a new chapter in this old discourse—and this new chapter starts with a novel concept of the house.